2018
DOI: 10.1038/s41598-018-25062-y
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected infection outcomes of China-origin H7N9 low pathogenicity avian influenza virus in turkeys

Abstract: The China-origin H7N9 low pathogenicity avian influenza virus (LPAIV) emerged as a zoonotic threat in 2013 where it continues to circulate in live poultry markets. Absence of overt clinical signs in poultry is a typical LPAIV infection outcome, and has contributed to its insidious maintenance in China. This study is the first description of H7N9 LPAIV (A/Anhui/1/13) infection in turkeys, with efficient transmission to two additional rounds of introduced contact turkeys which all became infected during cohousin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 53 publications
0
72
0
Order By: Relevance
“…However, the clinical outcome was much milder than in the previous study when infection of turkeys with the same AIV H9N2 strain was exacerbated by concomitant respiratory pathogens [10]. Infections with LPAIV in gallinaceous poultry are usually asymptomatic if uncomplicated, but in turkeys the clinical disease caused by the virus alone is often observed [9,42]. The long duration of respiratory shedding and the robust antibody response indicate that the H9N2 virus may readily infect turkeys and induce only non-specific clinical signs, enabling the spread of the virus within a flock.…”
Section: Discussionmentioning
confidence: 71%
“…However, the clinical outcome was much milder than in the previous study when infection of turkeys with the same AIV H9N2 strain was exacerbated by concomitant respiratory pathogens [10]. Infections with LPAIV in gallinaceous poultry are usually asymptomatic if uncomplicated, but in turkeys the clinical disease caused by the virus alone is often observed [9,42]. The long duration of respiratory shedding and the robust antibody response indicate that the H9N2 virus may readily infect turkeys and induce only non-specific clinical signs, enabling the spread of the virus within a flock.…”
Section: Discussionmentioning
confidence: 71%
“…On the other hand, there have been LPAI outbreaks where clinical signs and even increased mortality were reported. Turkeys are more susceptible to LPAIV infection than broilers and laying hens (Mutinelli et al, 2003;Slomka et al, 2018). Similarly, the first signs in a Canadian outbreak of H7N3 LPAI were a sudden drop in feed consumption and a slight increase in mortality (Bowes et al, 2004).…”
Section: 2mentioning
confidence: 99%
“…Experimental infections with LPAI H7N9 strain A/Anhui/ A/2013 revealed that the virus is highly tropic for the upper respiratory tract in poultry (Pantin-Jackwood et al, 2014). However, Slomka et al (2018) have detected systemic dissemination of the LPAIV H7N9 subtype to multiple organs beyond the respiratory and digestive tracts, including skeletal muscles and feather follicles in experimentally infected turkeys. The presence of the virus was detected by immunohistochemistry and mostly in specimens collected from turkeys infected with a high dose of the virus (8 log 10 EID 50 ).…”
Section: Assessment Of Lpaiv Transmission Via Raw Poultry Meatmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a more recently designed RT-qPCR which amplifies elsewhere within the MP-segment was validated [24] and featured successfully in subsequent AIV outbreaks and wild bird investigations [25][26][27][28], AIV in vivo studies [29,30] and SwIV field investigations [31][32][33][34]. The importance of appropriate test validation has been emphasised in a veterinary context [35], with an MP-segment RT-qPCR for generic detection of contemporary H1N1, H1N2 and H3N2 SwIV subtypes in European pigs having been also validated [36].…”
Section: Introductionmentioning
confidence: 99%